A Bioinspired Functionalization of Polypropylene Separator for Lithium-Sulfur Battery - Zhang, Zhijia (Polymers (Basel), 2019)
Lithium-sulfur batteries have received intensive attention, due to their high specific capacity, but the shuttle effect of soluble polysulfide results in a decrease in capacity. In response to this issue, we develop a novel tannic acid and Au nanoparticle functionalized separator. The tannic acid and gold nanoparticles were modified onto commercial polypropylene separator through a two-step solution process. Due to a large number of phenolic hydroxyl groups contained in the modified layer and the strong polarity of the gold nanoparticles, the soluble polysulfide generated during battery cycling is well stabilized on the cathode side, slowing down the capacity fade brought by the shuttle effect. In addition, the modification effectively improves the electrolyte affinity of the separator. As a result of these benefits, the novel separator exhibits improved battery performance compared to the pristine polypropylene separator.